2022
DOI: 10.3928/1081597x-20221018-02
|View full text |Cite
|
Sign up to set email alerts
|

Topical Losartan for Treating Corneal Fibrosis (Haze): First Clinical Experience

Abstract: PURPOSE: To report the first clinical experience with topical losartan for treating a case of severe corneal haze after complicated laser in situ keratomileusis (LASIK). METHODS: A 36-year-old woman presented with corneal haze in the left eye after femtosecond laser–assisted LASIK. The left eye had flap dislocation and significant striae, which had been re-lifted. Uncorrected distance visual acuity (UDVA) was 20/200 and corrected distance visual acuity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Even when this treatment is effective in closing a PED, however, the affected cornea frequently has moderate to severe scarring stromal fibrosis that limits the vision in the eye. Several recent rabbit studies, 38 40 as well as a clinical report in humans, 41 , 42 have demonstrated the efficacy of topical losartan in decreasing stromal myofibroblasts and fibrosis after a variety of corneal injuries. It may be that combined topical Oxervate and topical losartan could provide the best treatment for neurotropic corneas with a PED and stromal scarring fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Even when this treatment is effective in closing a PED, however, the affected cornea frequently has moderate to severe scarring stromal fibrosis that limits the vision in the eye. Several recent rabbit studies, 38 40 as well as a clinical report in humans, 41 , 42 have demonstrated the efficacy of topical losartan in decreasing stromal myofibroblasts and fibrosis after a variety of corneal injuries. It may be that combined topical Oxervate and topical losartan could provide the best treatment for neurotropic corneas with a PED and stromal scarring fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…I would recommend initiating treatment with 0.8 mg/mL losartan drops 6 times a day in the eye with the herpes zoster scar. 1–3 I would continue that treatment for at least 6 months, along with oral valacyclovir to prevent recurrence of the infection because antiherpetics have been shown to be effective in both herpes zoster and herpes simplex keratitis reactivation. Importantly, several case reports in humans not yet published have responded to topical losartan even years after the original injury.…”
Section: Steven E Wilson MDmentioning
confidence: 99%
“…Although in our environment we do not currently have this therapeutic option and, therefore, we do not yet have experience with it, there are already described in the literature cases of haze improved or resolved with the application of topical losartan 4 to 6 times a day, for at least 6 months, without appearing to pose any additional risk to the patient. 4 Based on this, this topical pharmacological treatment could be considered before deciding on a surgical option, although it is true that in this very young patient, with the other eye with hardly any visual acuity, we could enter into the moral conflict of what is more beneficial for the patient, whether to delay a possible recovery of visual acuity by trying a more conservative and time-consuming pharmacological treatment or directly opting for surgery, with the most appropriate technique based on the characteristics that we have previously described. In our opinion, it is important to weigh the physical and psychological risks/benefits of this patient and his family and involve them in the decision.…”
Section: Fernando Llovet MD Phdmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rabbits supported the efficacy of topical losartan in decreasing scarring fibrosis after Descemetorhexis, alkali burn, and photorefractive keratectomy injuries, and in case reports of humans with scarring fibrosis after surgical complications. Clinical studies are needed to explore the efficacy and safety of topical losartan in the prevention and treatment of corneal scarring fibrosis, and other eye disorders where TGF beta has a role in pathophysiology [39–42,43 ▪▪ ].…”
Section: Managementmentioning
confidence: 99%